Chinese military modernization and force development a Western perspective - Cordesman, Anthony H.; Hess, Ashley; Yarosh, Nicholas S. (Center for Strategic and International Studies, 2013)
China's military development has become a key focus of US security policy as well as that of virtually all Asia-Pacific states. This report examines trends in Chinese strategy, military spending, and military forces based on Chinese defense white papers and other official Chinese sources; US reporting by the Department of Defense and other defense agencies; and other government sources, including Japanese and Korean defense white papers and the International Monetary Fund. The analysis also draws on the work of experts outside of government, various research centers, and nongovernmental organizations. The goal is to provide a comparison of different views and sources, contrasting Chinese and outside views and highlighting the trends where adequate data are available, as well as the problems, gaps, and contradictions in various sources. The report is not intended to provide a particular view of Chinese developments or policy recommendations, but rather to act as a reference that can be used in US and Chinese military dialogue and by other experts looking for a comparison of official sources and the trends in Chinese forces